The Use of Expressive Speech Acts by A Tourette Syndrome in Front of the Class Movie - Nestiani Hutami; Nurul Khasanah Rahmawati (Universitas Brawijaya, 2020)
Expressing feelings or emotions is as important as meaning in speaker’s utterances. It is more interesting when the speaker is a Tourette syndrome sufferer. This study aims to examine how Expressive speech acts are used by the main character, Brad Cohen, in Front of the Class movie suffering from Tourette syndrome to communicate with other people around him. The study employs a descriptive qualitative approach. Data were taken from the utterances of the main character that further were classified into six Expressive speech acts proposed by Searle. The results of this study show two conditions which are either how relaxing or how stressful the main character interacts with other people. The Expressive speech acts that Brad uses to express his relaxing feeling are ‘thank’, ‘congratulate’, and ‘welcome’. On the other hand, the Expressive verbs that Brad uses because he feels upset or stressful are ‘thank’ ‘apologize’, ‘condole’, and ‘deplore’. Moreover, one Expressive verb that seems to fit into both situations is ‘thank’. In this case, it depends on the situation although eventually its purpose is the same which is expressing gratitude.